[Драмы. Проза] - Лермонтов Михаил Юрьевич (1990)
Заглавие тома составлено на основе анализа содержания Экземпляры: ф.6 (1997) / Инвентарный номер: 39378 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Л 49 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)1